Atributos químicos e físicos do solo e produtividade de soja em agricultura convencional e de precisão - Queiroz, Fernando Nakayama de (2011)
The fundamental principles of precision agriculture are to increase crop productivity and to maintain agricultural sustainability through the use of fertilizer material on a variable rate, unlike the conventional farming, which uses values based on the average use of inputs. The aim of this study was to make a comparison between conventional farming (AC) and precision farming (AP), taking into account the chemical attributes available in the soil and its physical characteristics. The experiment was conducted in an area of 19.63 ha, in Cascavel, Paraná. Three bands were defined for conventional agriculture and three for precision agriculture. To create theme maps, kriging was used as interpolator, and the spatial dependence data were evaluated through semivariograms. Soybean yield was highly correlated with K in both cropping systems, but was lightly correlated with the remaining attributes evaluated. In AC it was found that the attributes yield, clay, sand, Cu, and cone index 0-20 cm showed strong spatial dependence. The remaining attributes presented weak and moderated spatial dependence. For the AP system, Cu presented strong spatial dependence. With exception to Zn, all the evaluated attributes were in availability levels for soy development, and this fact influenced the AP yield not to be significantly higher than AC. The interpolated yield mean was virtually the same for both systems, and in most of the area (59,7%) AP showed higher productivity than AC.